2021
DOI: 10.3390/polym13142228
|View full text |Cite
|
Sign up to set email alerts
|

Citrate-Coated Magnetic Polyethyleneimine Composites for Plasmid DNA Delivery into Glioblastoma

Abstract: Several ternary composites that are based on branched polyethyleneimine (bPEI 25 kDa, polydispersity 2.5, 0.1 or 0.2 ng), citrate-coated ultrasmall superparamagnetic iron oxide nanoparticles (citrate-NPs, 8–10 nm, 0.1, 1.0, or 2.5 µg), and reporter circular plasmid DNA pEGFP-C1 or pRL-CMV (pDNA 0.5 µg) were studied for optimization of the best composite for transfection into glioblastoma U87MG or U138MG cells. The efficiency in terms of citrate-NP and plasmid DNA gene delivery with the ternary composites could… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…In tumor diagnostics and treatment, nanoparticles have recently become more important and function as diagnostic markers [ 16 , 17 , 18 ] and drug delivery devices [ 19 , 20 , 21 , 22 , 23 ]. There are several trials in which it has been shown that nanoparticles help detecting tumor tissue via photoimaging [ 17 , 24 ] and can deliver chemotherapeutics to the tumor sites [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In tumor diagnostics and treatment, nanoparticles have recently become more important and function as diagnostic markers [ 16 , 17 , 18 ] and drug delivery devices [ 19 , 20 , 21 , 22 , 23 ]. There are several trials in which it has been shown that nanoparticles help detecting tumor tissue via photoimaging [ 17 , 24 ] and can deliver chemotherapeutics to the tumor sites [ 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%